Pengaruh Penggunaan Media Komik Materi Bilangan Cacah Terhadap Hasil Belajar Siswa Kelas II SDN 01 Koto Baru - Fillahanasari, Eka; Ningsih, Sri Yuminar; Arinda, Sosi (Universitas Batanghari Jambi, 2024)
The aim of this research is to overcome students' low interest in learning about whole numbers. To overcome this, interesting and appropriate media is needed so that students can easily understand the material. Therefore, researchers will apply comic media. The type of research used is quantitative research with a Quasi Experimental Design approach. This research was carried out at SDN 01 Koto Baru Class IIA and IIB in the even semester of the 2023/2024 academic year. The population in this study was 15 Class IIA students and 15 Class IIB students from this elementary school. Data collection used uses independent and dependent variables. Development of instruments used for validity testing, reliability testing, level of difficulty testing. The data collection technique used was a preliminary test (Pritest) with a final test (post-test). The data analysis technique for this research uses the Normality Test, homogeneity test and hypothesis test. Based on the results obtained, the significance obtained by the experimental class IIA was 0.004<0.05, meaning that there was an influence of comic media on student learning outcomes in Mathematics content on Whole Numbers. Meanwhile, the results of the paired samples t test showed that the significance obtained by the control class IIB was 0.115<0.05, meaning that there was no influence on student learning outcomes for the Mathematics content on Whole Numbers. This means that it can be concluded that comic media is good for application in second grade for Mathematics content.